The Role of Spirituality in Living with Disabilities - Zhang, Dongdong (Journal of religion, disability & health, 2005)
This paper reviews the existing literature on the role of spirituality in the experiences of people with disabilities as well as parents of children with disabilities. Spirituality appears to provide meanings, inner strength, peace, and hope to both groups of individuals. In addition, many experience self-transformation through living with disability, becoming more mature and compassionate. Future research is needed to explore the deeper role of spirituality to expand and deepen our understanding of the core nature of spirituality in living with disabilities. There is also a need for research on how to integrate spirituality into the practice of working with individuals with disabilities as well as families of children with disabilities.